Pemanfaatan Model Tutorial Berbasis Komputer di SMP Islam Terpadu Ibnu Halim Kec. Medan Deli - Novanty, Icha; Wahyuni, Sri; Sijabat, Sutoni; Zulfahmi, Zulfahmi (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
Computer-based learning is complete learning, so students must understand the material delivered through computer media. Computer-based learning consists of four types. Namely training and practice models, tutorial models, simulation models, and game models. Of the four types of models, the tutorial model has its own advantages compared to other types of models.Â Keywords : computer-based learning, tutorial models, types